2020
DOI: 10.1111/ajad.12986
|View full text |Cite
|
Sign up to set email alerts
|

Does Cannabis Dependence Add on to the Neurocognitive Impairment Among Patients With Opioid Dependence? A Cross‐Sectional Comparative Study

Abstract: Background and Objectives Chronic opioid exposure has been linked with neurocognitive impairments. Evidence of residual impairment with cannabis use is less consistent. We investigated whether patients with opioid and cannabis dependence perform poorly compared with those with opioid dependence alone. Methods We recruited three groups of participants aged 18 to 55 years: opioid and cannabis dependence (OCaD; n = 21), only opioid dependence (OD; n = 19), and a control group (HC; n = 20). Subjects with other sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The reason for retaining tobacco and cannabis dependence was the high comorbidity of these disorders with opioid dependence; hence, excluding these participants would have compromised the study’s generalizability. 18 , 19 Patients with HIV, hepatitis C, or other medical comorbidities were also included. However, patients with severe mental illness, intellectual disability, or organic brain disease were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The reason for retaining tobacco and cannabis dependence was the high comorbidity of these disorders with opioid dependence; hence, excluding these participants would have compromised the study’s generalizability. 18 , 19 Patients with HIV, hepatitis C, or other medical comorbidities were also included. However, patients with severe mental illness, intellectual disability, or organic brain disease were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…68, 70 Two studies examined cognitive functions and found significant differences in perceptual-motor functioning, but not intelligence, between users and healthy controls. 67, 74 In terms of methodological weaknesses, two studies utilized existing case notes and were prone to limitations of secondary data and recall biases. 68, 70 Use of basic cannabis-use screening measures was found in four studies.…”
Section: Psychological and Psychiatric Correlates Of Cannabis Usementioning
confidence: 99%
“…68, 70 Use of basic cannabis-use screening measures was found in four studies. 69, 71–72,74 Apart from two studies, the remaining six had very small sample sizes as well.…”
Section: Psychological and Psychiatric Correlates Of Cannabis Usementioning
confidence: 99%
See 1 more Smart Citation
“…5 Potential risks that may accompany legalization include an increase in users, 6 youth exposure, driving impairment, and cannabis use in sensitive occupations. 7 On October 17, 2018, Canada became the first country of high socioeconomic status to legalize selling and using cannabis for recreational purposes. Research suggests that media influences public perception and priorities surrounding an issue, 8,9 and the media's portrayal of this policy change provides an opportunity to discern which issues were presented most prominently to the public regarding cannabis legalization.…”
Section: Introductionmentioning
confidence: 99%